Highly efficient steam reforming of ethanol (SRE) over CeO x grown on the nano Ni x Mg y O matrix: H 2 production under a high GHSV condition - Luo, Xiang; Hong, Yu; Zhang, Honglei; Shi, Kaiqi; Yang, Gang; Wu, Tao (Wiley, 2019)
Steam reforming of ethanol (SRE) over non-noble metal catalysts is normally conducted at high temperature (>600°C) to thermodynamically favour the catalytic process and carbon deposition mitigation. However, high temperature inhibits water-gas shift reaction (WGSR) and therefore restrains the yield of H2 and leads to the formation of an excessive amount of CO. The modification of non-noble metal catalyst to enhance WGSR is an attractive alternative. In this study, CeOx was firstly loaded onto a nano-scaled NixMgyO matrix and subsequently used as the catalyst for hydrogen production via SRE. Morphology of the catalyst materials was characterized by using a series of technologies, while H2-temperature programmed reduction (H2-TPR), CO-temperature programmed deposition (CO-TPD), and X-ray photoelectron spectroscopy (XPS), were employed to study the surface nickel, ceria clusters, and their interactions. The catalytic activity and durability of the catalyst were studied in the temperature region of 500°C to 800°C. The CeOx-coated nano NixMgyO matrix exhibited an outstanding hydrogen yield of 4.82 mol/molethanol under a high gas hourly space velocity (GHSV) of 200 000 hour−1. It is found that the unique Ni0-CeOx structure facilitates the adsorption of CO on the surface and therefore promotes the effective hydrogen production via WGSR. Moreover, this modified NixMgyO matrix was found to be a more robust and anticoking nanocatalyst because of reversible switch between Ce4+ and Ce3+. © 2019 John Wiley & Sons, Ltd.